Teachers’ Remuneration and Students’ Involvement in Public Secondary Schools in Southwest, Nigeria - Ajadi, Olugbenga Timothy (Innovare Journal of Education, 2024)
Student involvement is a central aspect of effective teaching. This is because students are central to the main reason why teachers are employed and, more so, the reason for school establishment. As a result, this study investigated regular teachers’ remuneration, the level of students’ involvement, and the influence of teachers’ remuneration on student involvement in public secondary schools in southwest states of Nigeria. The study population comprised all teachers in the public secondary schools in southwest states of Nigeria. A sample size of 1,080 was calculated and derived using Research Advisor’s Table at 95% degree of confidence with a 5% error margin. The questionnaire was used to elicit information from respondents. The study found that teachers’ remuneration is not promptly and regularly paid. In addition, the level of student involvement is low and teachers’ remuneration significantly influences student involvement in public secondary schools in southwest states in Nigeria. It was recommended that teachers’ remuneration be paid promptly and regularly and that the government improve teachers’ service conditions by increasing their remuneration to reflect the economic reality in Nigeria.